2014
DOI: 10.1111/nan.12083
|View full text |Cite
|
Sign up to set email alerts
|

Dithiocarb (N,N‐diethyldithiocarbamate, DEDTC) decreases levels of biogenic monoamines in the adult mouse brain

Abstract: Our data suggest that DEDTC provokes alterations in biogenic amines and in different substrates of neurotransmitter systems, which could explain some of the neurobehavioural effects observed in patients treated with disulphiram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Karimov and coworkers declared that diethyldithiocarbamate derivatives exhibited an inhibitory effect on carbonic anhydrases (CA I and CA II), α‐glucosidase, AChE, and BChE enzymes [64] . The study stated that the level of choline acetyltransferase decreased after the dithiocarb treatment in mice compared to control animals [65] . Kumar group reported that administration of natrium diethyl dithiocarbamate trihydrate decreased the level of AChE activities in comparison to the disease control rats in the brain homogenate of experimental animals [66] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Karimov and coworkers declared that diethyldithiocarbamate derivatives exhibited an inhibitory effect on carbonic anhydrases (CA I and CA II), α‐glucosidase, AChE, and BChE enzymes [64] . The study stated that the level of choline acetyltransferase decreased after the dithiocarb treatment in mice compared to control animals [65] . Kumar group reported that administration of natrium diethyl dithiocarbamate trihydrate decreased the level of AChE activities in comparison to the disease control rats in the brain homogenate of experimental animals [66] .…”
Section: Resultsmentioning
confidence: 99%
“…[64] The study stated that the level of choline acetyltransferase decreased after the dithiocarb treatment in mice compared to control animals. [65] Kumar group reported that administration of natrium diethyl dithiocarbamate trihydrate decreased the level of AChE activities in comparison to the disease control rats in the brain homogenate of experimental animals. [66] When the results of various studies are examined, it is seen that the substances synthesized by our study group are promising molecules in inhibiting the studied enzymes.…”
Section: Biochemical Resultsmentioning
confidence: 99%